Direct generation of high brightness path entangled N00N states using structured crystals and shaped pump beams - Domenico, Giuseppe Di; Pearl, Shaul; Karnieli, Aviv; Trajtenberg-Mills, Sivan; Juwiler, Irit; Eisenberg, Hagai S.; Arie, Ady (Opt. Express, OE, 2022)
Optical N00N states are N-photon path entangled states with important applications in quantum metrology. However, their use was limited till now owing to the difficulties of generating them in an efficient and robust manner. Here we propose and experimentally demonstrate two new simple, compact and robust schemes to generate path entangled N00N states with N = 2 that emerge directly from the nonlinear interaction. The first scheme is based on shaping the pump beam, and the second scheme is based on modulating the nonlinear coefficient of the crystal. These new methods exhibit high coincidence count rates for the detection of a N00N state, reaching record value of 2 × 105 coincidences per second. We observe super-resolution by measuring the second order correlation on the generated N = 2 state in an interferometric setup, showing the distinct fringe periodicity at half of the optical wavelength. Our findings may pave the way towards scalable and efficient sources for super-resolved quantum metrology applications and for the generation of bright squeezed vacuum states.
Publisher: Optica Publishing Group
Keywords: Nonlinear optical crystals; Phase shift; quantum information; Single mode fibers; Squeezed states; Superconducting nanowire single photon detectors